Characteristics and identification of multi-enzyme producing bacterial strain isolated from the gastrointestinal tract of milkfish Chanos chanos forskal. - Legario, Francis S.
Beneficial bacteria in the digestive tract of fishes are least studied because the focus of microbiological investigations in this field has been primarily on harmful or pathologic bacteria. The aim of the study is to isolate, charactrize and identify the bacterial strain isolated from the gut of adult milkfish (weighing approximately 250 g) Chanos chanos Forsskal cultured in pond with green filamentous algae (Chaetomorpha sp.) diet. The bacterial strain was isolated from the anterior intestine of milkfish. It showed characteristics colony pattern, Gram-stain reaction, endospore formation and motility belonging to Genus Bacillus. Scanning electron microscopy confirmed the characteristic rod-shape morphology. Physiological testing revealed that the isolate is able to tolerate both aerobic and anaerobic conditions, that it can grow at temperatures ranging from 30-40 degrees centigrade, can tolerate salt concentration of 0-40 ppt and pH levels of 5-9. In bile tolerance test, it is able to grow at different bile concentrations indicating it as part of the intestinal flora. The bacterial isolate is oxidase negative but catalase positive. The isolate is able to degrade L-arginine, L-tryptophan, sodium pyruvate and gelatin. It is able to utilize citrate as carbon source and also to produce acid from glucose. The isolate can reduce nitrate. The isolate was tested for its ability to ferment 49 carbohydrates using the API 50CH (bioMerieux, Inc). The isolate is able to ferment glycerol, ribose, D-glucose, N-acetylglucosamine, arbutin, esculin, salicin, D-cellobiose, D-maltose, D-trehalose, amidon (starch), and glycogen. The isolate was further tested for activities of extracellular enzymes such as total carbohydrolase, alpha amylase, cellulase, phytase, lipase, and protease. The isolate exhibited high proeolytic enzyme activity of 3.25 U/mg protein. It also exhibited moderate activities of lipase and cellulase, namely 0.52 and 0.38 U/mg protein, respectively. Total carbohydrolase, alpha amylase and phytase activities were 0.002, 0.0054, and 0.001 U/mg, respectively. Based on these results, the isolate is 95 percent similar to bacillus cereus in this identification system. BLAST analysis of the 16S rRNA gene sequence showed that the isolate is 99 percent similar to Bacillus cereus ATCC 14579t (type strain). Multiple sequence alignment using MEGA5 and clustalW2 showed that the isolate is most closely related to B. cereus ATCC 14579t. Results putatively identified the isolate as Bacillus cereus strain.